2018
DOI: 10.3126/nepjoph.v10i1.21691
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and visual outcome, prognostic factor, visual acuity and globe survival in posterior segment intraocular foreign body at Tilganga Institute of Ophthalmology

Abstract: Purpose: To evaluate clinical characteristics, visual outcomes and globe survival after intraocular foreign body removal from posterior segment via pars plana approach. Methods: A hospital based retrospective study. All the patients of penetrating eye injury with intraocular foreign body in posterior segment as detected by computed tomography were enrolled from 2012 to 2014.Results: Thirty patients of 30 eyes were included. The mean age was 27.7 years. (2-52). Twenty-four (80%) were male. Out of 30 eyes 19 (63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
(7 reference statements)
1
1
1
2
Order By: Relevance
“…We found that majority of patients with IOFB were young with mean age of 27.7 years and median of 28 years. This finding is similar to the findings of several authors [6].…”
Section: Discussionsupporting
confidence: 94%
“…We found that majority of patients with IOFB were young with mean age of 27.7 years and median of 28 years. This finding is similar to the findings of several authors [6].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, RD was observed in 22.01% of eyes with IOFBs. Similarly, Sharma et al (2018) reported RD in 30% of cases [9]. Despite a higher RD incidence post-trauma, our study found no association between RD and visual outcomes.…”
Section: Outcomes and Factors Affecting Nal Vacontrasting
confidence: 57%
“…Posterior segment IOFBs are commonly linked with complications like retinal detachment, endophthalmitis, and vitreous hemorrhage [9]. Earlier reports documented endophthalmitis incidence in IOFB cases ranging from 0.00-16.55% (mean = 6.65%).…”
Section: Outcomes and Factors Affecting Nal Vamentioning
confidence: 99%
“…Травма глаза всегда связана с риском серьезных медицинских последствий, среди которых особое место отводится снижению остроты зрения вплоть до односторонней или двусторонней слепоты [4]. Кроме того, травма органа зрения несет в себе бремя прямых и косвенных экономических потерь, обусловленных не только временной и стойкой нетрудоспособностью пострадавших, но и затратами на оказание медицинской помощи [5].…”
Section: Ophthalmology In Russia 2020;17(2):181-187unclassified
“…[73]. Однако, по признанию исследователей, использование предложенных способов прогнозирования в практической работе невозможно из-за двух проблем: низкого удельного веса выявленных факторов риска и сложности объективизации критериев, оценивающих степень тяжести повреждения [74][75][76][77][78]. В качестве примера можно привести обзор 2000 года, авторы которого предприняли попытку предикции посттравматического инфекционного эндофтальмита и пролиферативной витреоретинопатии у 130 пациентов при травмах глаз, вызванных внутриглаз-ными или ретробульбарными инородными телами [79].…”
Section: Ophthalmology In Russia 2020;17(2):181-187unclassified